Unsystematic disposal of facemasks and related environmental health threats during Covid-19 in Sri Lanka - Ruzaik, Fareena (Department of Demography, UoC., 2022)
The Covid-19 outbreak negatively affected the entire world in terms of its sociocultural, economic and environmental dimensions; killing 800,000 people and infecting 22.7 million, which includes 45,000 deaths and 3,000,000 infected cases in Sri Lanka. Social distancing, hand washing, sanitizing and wearing face masks are preliminary precautionary actions frequently announced by the health authorities in Sri Lanka. Ultimately, the last became a mandatory requirement in public gatherings and public places, which was closely monitored by security officials. The government and private sector organizations imported and manufactured a variety of masks to meet these higher demands. Out of which, 60- 70 percent are one-time usable facemasks. Consequently, the unsystematic disposal of face masks to the environment has become a large threat to environmental health including the health of the general public. Sri Lankan health authorities and health professionals provide frequent announcements to adhere to health instructions to avoid the spread of this novel coronavirus, under the provision of Quarantine and Prevention of Diseases Law No. 12 of 1952; whereas equal importance and guidance have not been given in terms of its disposing or recycling masks in a safe manner since most of these masks contain plastics and are made of petroleum-based non-renewable polymers that are nonbiodegradable, hazardous to the environment, and create health issues. One of the areas, where the environmental impacts of COVID-19 are most pronounced, is in waste management .
The study is to assess the possible environmental threats caused by the unsystematic disposal of used facemasks during Covid-19 pandemic in Sri Lanka.
Keywords: Covid19, facemask, unsystematic, environmental issues